Identification, capture, and biotelemetry of socially living monkeys - Rasmussen, K.L.R. (NIH Animal Center, Poolesville, MD) (Laboratory animal science (Chicago), 1991)
Remote monitoring of physiologic function using socially living monkeys differs from that using individually housed animals in that access to subjects may be limited. Some logistic aspects of working with socially housed monkeys are reviewed, including identification of individuals and capturing subjects. Methods of remote sampling include hormonal assays of urine and fecal samples, measurement of physical indices as estimates of reproductive status, and the use of telemetry devices to record activity and biopotentials. Key factors in the selection of a telemetry system are discussed. In many cases, remote monitoring may permit assessment of physiologic function without the stress of handling or restraint